Evaluation of the Phosphorus Load on Freshwater Bodies of Subjects of the Russian Federation: Modeling of the Migration of Phosphorus and Its Compounds among Environmental Components - Tarasova, N. P.; Makarova, A. S.; Vasileva, E. G.; Shlyakhov, P. I.; Zanin, A. A. (Doklady earth sciences, 2018)
This article is devoted to a model of the migration of phosphorus and its compounds between the components of the environment and the evaluation of the phosphorus load on freshwater bodies on the scale of the subjects of the Russian Federation. The results of calculations described in this article show that a number of the subjects of the Russian Federation are susceptible to a high and extremely high risk of a negative impact of anthropogenic phosphorus on freshwater bodies.